Incorporating chaotropic/kosmotropic chemistries onto plasmonic nanoheater to boost steam generation beyond its photothermal property - Chong, Carice (2023)
Photothermal steam generation promises decentralized water purification, but current methods suffer from slow water evaporation even at high photothermal efficiency of ≈98%. This drawback arises from the high latent heat of vaporization that is required to overcome the strong and extensive hydrogen bonding network in water for steam generation. Here, light-to-vapor conversion is boosted by incorporating chaotropic/kosmotropic chemistries onto plasmonic nanoheater to manipulate water intermolecular network at the point-of-heating. The chaotropic-plasmonic nanoheater affords rapid light-to-vapor conversion (2.79 kg m-2  h-1  kW-1 ) at ≈83% efficiency, with the steam generation rate up to 6-fold better than kosmotropic platforms or emerging photothermal designs. Notably, the chaotropic-plasmonic nanoheater also lowers the enthalpy of water vaporization by 1.6-fold when compared to bulk water, signifying that a correspondingly higher amount of steam can be generated with the same energy input. Simulation studies unveil chaotropic surface chemistry is crucial to disrupt water hydrogen bonding network and suppress the energy barrier for water evaporation. Using the chaotropic-plasmonic nanoheater, organic-polluted water is purified at ≈100% efficiency, a feat otherwise challenging in conventional treatments. This study offers a unique chemistry approach to boost light-driven steam generation beyond a material photothermal property.